Alberta High School Counsellors’ Knowledge of Homosexuality and Their Attitudes Toward Gay Males - Alderson, Kevin; Orzeck, Tricia; McEwen, Scott (Canadian Journal of Education/Revue canadienne de l'éducation, 2009)
In this study we investigated Alberta high school counsellors’ knowledge about homo‐ sexuality and their attitudes toward gay males. Three questionnaires were mailed to 648 high school counselling centres; 223 individuals returned the completed questionnaires. Most counsellors attained low scores in measured homo‐negativity and high scores regard‐ ing knowledge of homosexuality. Results from a Pearson correlational analysis indicated a negative significant relationship between the level of knowledge about homosexuality and homo‐negativity, supporting other researchers’ findings that higher levels of knowledge may be accompanied by more positive attitudes. Key words: homosexual males, beliefs, mental health professionals Les auteurs ont analysé les connaissances de conseillers d’orientation scolaire du second‐ aire au sujet de l’homosexualité et leurs attitudes vis‐à‐vis des gais. Trois questionnaires ont été postés à 648 centres d’orientation ; 223 personnes ont retourné les questionnaires dûment remplis. La plupart des conseillers d’orientation ont obtenu des scores faibles pour l’homonégativité et des scores élevés pour les connaissances au sujet de l’homosexualité. Les résultats d’une analyse corrélationnelle indiquent un net lien négatif entre le niveau de connaissances sur l’homosexualité et l’homonégativité, ce qui corrobore les conclusions d’autres chercheurs selon lesquelles de meilleures connaissances peuvent s’accompagner d’attitudes plus positives. Mots clés : homosexuels, croyances, professionnels de la santé mentale